Beyond the pandemic: Transforming food systems after COVID-19 - Swinnen, Johan; McDermott, John; Yosef, Sivan; Díaz-Bonilla, Eugenio; Vos, Rob (International Food Policy Research Institute, 2021)
Food systems need to be transformed if we are to meet the Sustainable Development Goals and increase resilience of these systems to shocks. The pandemic has provided useful lessons on opportunities and weaknesses that must be addressed. KEY MESSAGES - Before the onset of the coronavirus pandemic, our food systems already faced serious challenges in achieving equitable access to healthy, nutritious food for all; environmental sustainability; and resilience to shocks. COVID-19 has put the world further behind in reaching the UN Sustainable Development Goals (SDGs). - COVID-19 caused widespread loss of livelihoods and incomes and reduced access to services, safety nets, and education, threatening the food security, health, and nutritional status of poor and marginalized people around the world. - Food system transformation must be pursued to regain this lost ground and achieve the SDGs by 2030. - Yet the pandemic and associated responses exposed weaknesses and inequalities within food systems, including among different world regions, rural and urban communities, rich and poor populations, and disadvantaged groups such as women. - Some food systems and sectors were more resilient than others, depending on their structure, governance, and roles of the public and private sector. - 2020 offered lessons, innovations, and opportunities that can help make food systems more resilient to future shocks and more inclusive, efficient, sustainable, and healthy.